Contextul de învățare, determinantă a eficienței procesului de formare profesională prin învățământul universitar [Articol] - Dandara, Otilia; Gogoi, Elena (CEP USM, 2024)
Higher education has evolved over time, being responsive to society’s needs and responding to sociocultural conditions anchored in time. The quality and efciency of professional training through higher education has always been determined by a series of factors, which in all their inﬂuence, generated a conceptual approach in which the educational process was subordinated to certain principles and was carried out according to clearly outlined methodologies. The teacher and the student, the two actors carry out their activity in a certain learning/ educational context, which essentially constitutes the basic condition for the realization of the educational paradigm. The relationship between the educational paradigm and the learning context is a complex and inter-determining one, a phenomenon that has been studied less, and even more, we could say that it has been neglected. In the current conditions, marked by the increasing need to bring the university environment closer to the labour market, we consider it necessary to take advantage of all the possibilities of the training paradigm based on the problems of the labour market and the educational context in which this paradigm becomes applicable.
THE LEARNING CONTEXT, KEY FACTOR OF PROFESSIONAL TRAINING PROCESS EFFICIENCY THROUGH UNIVERSITY EDUCATION
Keywords: higher education; learning/educational context; paradigm